Schottky-type grain boundaries in CCTO ceramics - Felix, A. A. [UNESP]; Orlandi, Marcelo Ornaghi [UNESP]; Varela, José Arana [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
In this work we studied electrical barriers existing at CaCu(3)Ti(4)O(12) (CCTO) ceramics using dc electrical measurements. CCTO pellets were produced by solid state reaction method and X-ray diffractograms showed which single phase polycrystalline samples were obtained. The samples were electrically characterized by dc and ac measurements as a function of temperature, and semiconductor theory was applied to analyze the barrier at grain boundaries. The ac results showed the sample's permittivity is almost constant (10(4)) as function of temperature at low frequencies and it changes from 100 to 10(4) as the temperature increases at high frequencies. Using dc measurements as a function of temperature, the behavior of barriers was studied in detail. Comparison between Schottky and Poole-Frenkel models was performed, and results prove that CCTO barriers are more influenced by temperature than by electric field (Schottky barriers). Besides, the behavior of barrier width as function of temperature was also studied and experimental results confirm the theoretical assumptions. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: CCTO; Grain boundary; Potential barrier; Schottky model